Combination treatment for type 2 diabetes mellitus (T2DM) : dipeptidyl peptidase-4 inhibitors (DPP-4) and metformin - Erna Kristin (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
Using the concept of inhibition of dipeptidyl peptidase-4 (DPP-4) as a new treatment for type 2 diabetes mellitus (T2DM) is based on the inhibition of bioactive peptide inactivation process. Most clinical trials on DPP-4 inhibition are based on vildagliptin, sitagliptin, saxagliptin, and linagliptin. The drugs may improve glycemic control when they are given as a combination with other oral hyperglycemic agents or when they are given to patients who received metformin and still had inadequate glycemic control. Studies showed that vildagliptin was well-tolerated if it was given as add-on treatment to metformin for 24 weeks duration. In addition, vildagliptin showed significant clinical improvement proven by the associated decrease in HbA1c and fasting glucose levels. Sitagliptin in initial combination therapy with metformin decreased HbA1c level by 2.1% after 24 weeks of treatment. It was reported that DPP-4 inhibitor saxagliptin increased glycemic control when it was added to metformin. The study included 743 patients with an average HbA1c level of 8.0% when they were treated with metformin alone. After 24 weeks of treatment, saxagliptin decreased HbA1c level by 0.7%. A multicenter, randomized, placebo-controlled, double-blind, parallel-group study examined the efficacy and tolerability of linagliptin as treatment adjunctive to metformin in patients T2DM. The primary end point was changed in HbA1c from baseline to 24 weeks of treatment. The mean adjusted change from baseline in HbA1c in the linagliptin group was 0.49% compared with an increase of 0.15% in the placebo group, with 26% and 9% of participants in the linagliptin and placebo groups, respectively, achieving an HbA1c 7.0% at 24 weeks. The combination of DPP-4 inhibitors and metformin has been shown to be well-tolerated with a very low risk of hypoglycemia. Therefore, DPP-4 inhibitors and metformin combination is an efficient, safe, and well-tolerated therapy for T2DM.